Graffiti: subculture or vandalism - Kurbatova T.N.; Vasilyeva R.S. (Психология и право, 2013)
The article discusses the phenomenon of the modern graffiti in terms of subculture and vandalism. We denote the boundary between the concepts of vandalism in cultural and legal discourse. Study of scientific sources and method of participant observation allowed us to offer our own definition of graffiti. Particular attention is paid to the psychological portrait of the graffiti painters on the basis of empirical data obtained for the first time in our country. The study compared groups of young people involved in graffiti and in legal fine arts. The study revealed the psychological characteristics of graffiti painters and identified the main factors that keep young people in the subculture. Graffiti subculture itself is not considered as a criminal community, but as a communicative field within which young people decide their age-specific problems. Accordingly, we proposed penalties for graffiti painters considering their psychological characteristics.